Double interface regulation: Toward highly stable lithium metal anode with high utilization. Issue 7 (13th February 2022) - Wang, Guanyao; Zhu, Ming; Zhang, Ying; Song, Chan; Zhu, Xiaolong; Huang, Zhongyi; Zhang, Yuanjun; Yu, Fangfang; Xu, Gang; Wu, Minghong; Liu, Hua‐Kun; Dou, Shi‐Xue; et al.
Abstract: The undesirable Li dendrite growth and other knock‐on issues have significantly plagued the application of Li metal anodes (LMAs). Herein, we report that the synergistic regulation of double interfaces adjacent to the metallic Li anode can effectively prevent the dendritic Li growth, significantly improving the cycling performance of LMAs under harsh conditions including high current density and high depth of discharge. Thorough comparison of electrolytes demonstrated that 1 M lithium bis(fluorosulfonyl)imide (LiFSI) in 1, 2‐dimethoxyethane (DME) can yield a robust and lithiophobic LiF‐rich upper interface (solid electrolyte interphase). Besides, the Sb‐based buffer layer forms a lithiophilic lower interface on current collector. The synergy of the upper and lower interfacial engineering plays an important role for outstanding cyclability of LMAs. Consequently, the plating/stripping of Li can be stably repeated for 835 and 329 cycles with an average Coulombic efficiency (CE) above 99% at 1 and 3 mA h cm −2, respectively. Surprisingly, the Li||Li symmetric cell can even withstand the baptism of current density up to 20 mA cm −2 . The excellent performance validates that the facile synergistic regulating of interfaces adjacent to the metallic Li anode provides an effective pathway to stabilize LMAs. Abstract : A synergistic adjacent interface engineering to improve the cyclability of Li metal anodes (LMAs) is designed by regulating the initial Li nucleation behavior and inhibiting Li dendrite growth on cycling concurrently. The lithiophilic nucleation buffer and the robust lithiophobic solid electrolyte interphase (SEI) can endow the LMAs with excellent Coulombic efficiencies (CEs) and significantly prolonged lifespan under higher current densities and capacities.